ANALYSIS OF TOTAL FLAVONOID LEVEL AND ANTIOXIDANT ACTIVITY TEST PURPLE CABBAGE (BRASSICA OLERACEA L. VAR. CAPITATA F. RUBRA) AND WHITE CABBAGE (BRASSICA OLERACEA L. VAR. CAPITATA F. ALBA) ETHANOL EXTRACT USING DPPH METHOD (1,1-DIFENIL-2-PIKRILHIDRAZIL) - Any Guntarti; Ratna Yuningtyas; Hari Susanti; Zainab Zainab (Jurnal Farmasi Sains dan Praktis, 2021)
Antioxidants are compounds that are needed by the body to protect the body from free radical attacks that can trigger the emergence of degenerative diseases. One of the compounds that has free radical scavenger activity by inhibiting Reactive Oxygen Species (ROS) is flavonoids found in purple cabbage and white cabbage. This study aims to determine the total levels of flavonoids expressed as quercetin equivalent (EK) and antioxidant activity using the DPPH method (1,1-diphenyl-2- picrylhydrazyl). Identification of flavonoid compounds by Willstater test and determination of total flavonoid levels using spectrophotometry, AlCl3 reagent. Flavonoid levels were calculated using linear regression equations. Qualitative test for the presence of antioxidant activity using TLC and antioxidant activity test using the DPPH method with the parameter value of ES50. The qualitative test results showed that the ethanol extract of purple cabbage and white cabbage contained flavonoids. The total flavonoid content of ethanol extract of purple cabbage was 5.17% w/w (EK) and ethanol extract of white cabbage was 3.84% w/w (EK). Qualitative test with TLC showed antioxidant activity. The standard antioxidant activity values ​​of quercetin, ethanol extract of purple cabbage and white cabbage were 2.138±0.064 µg/mL; 154.445±0,999 µg/mL and 373.546±1.336 µg/mL. The antioxidant activity of purple cabbage is weak and white cabbage is very weak.